Financial and strategic analysis of ALROSA Group - Aliyeva, Fidan; Pham, Hoang Long; Rýdlová, Barbora, 1976-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
ABSTRACT The study seeks to do financial and strategic analysis of ALROSA Company Limited, a diamond mining company in Russia. The company is seen as the biggest diamond mining company The study contains strategic and financial analysis with data from the annual financial report of the company from 2015 up to 2021. ALROSA Group strategically maintains a global diamond market leadership through a focused approach on raw diamonds, efficient management, social responsibility, and environmental conservation. Facing competition from De Beers, Petra Diamonds, and Rio Tinto, ALROSA anticipates potential credit quality issues in 2022. A SWOT analysis reveals strengths in market position and consistent prospecting investment, but weaknesses tied to Russia's economic performance and digital risks. Opportunities include local diamond market control and growth in Europe and China, while threats involve high unemployment and climate-related regulations. Financially, ALROSA exhibits stability, positive gross profit, and liquidity ratios favoring short-term obligations. To endure market competition, the company must adapt to market dynamics, embrace technology, and sustain financial strength through efficient cost management and robust balance sheets.
Vedoucí práce: Hoang Long Pham
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses